2017
DOI: 10.1371/journal.pbio.2002039
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of starvation signaling in promoting growth and recovery

Abstract: Growing cells are subject to cycles of nutrient depletion and repletion. A shortage of nutrients activates a starvation program that promotes growth in limiting conditions. To examine whether nutrient-deprived cells prepare also for their subsequent recovery, we followed the transcription program activated in budding yeast transferred to low-phosphate media and defined its contribution to cell growth during phosphate limitation and upon recovery. An initial transcription wave was induced by moderate phosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…The PHO regulon comprises of several genes that respond to phosphate starvation, and maintains internal phosphate levels by balancing transport of Pi from the external environment, from within vacuolar stores, and the nucleus (Figure 5A) (Ljungdahl and Daignan-Fornier, 2012; Secco et al , 2012). Extensive studies have defined general cellular responses to phosphate limitation (Ogawa, DeRisi and Brown, 2000; Wykoff and O’Shea, 2001; Boer et al , 2003, 2010; Saldanha, Brauer and Botstein, 2004; Gresham et al , 2011; Levy et al , 2011; Choi et al , 2017; Gurvich, Leshkowitz and Barkai, 2017). In general, the PHO response is very sensitive to phosphate limitation, inducing rapidly to restore internal phosphate levels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PHO regulon comprises of several genes that respond to phosphate starvation, and maintains internal phosphate levels by balancing transport of Pi from the external environment, from within vacuolar stores, and the nucleus (Figure 5A) (Ljungdahl and Daignan-Fornier, 2012; Secco et al , 2012). Extensive studies have defined general cellular responses to phosphate limitation (Ogawa, DeRisi and Brown, 2000; Wykoff and O’Shea, 2001; Boer et al , 2003, 2010; Saldanha, Brauer and Botstein, 2004; Gresham et al , 2011; Levy et al , 2011; Choi et al , 2017; Gurvich, Leshkowitz and Barkai, 2017). In general, the PHO response is very sensitive to phosphate limitation, inducing rapidly to restore internal phosphate levels.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have long observed that trehalose increases upon phosphate starvation (Lillie and Pringle, 1980; Klosinska et al , 2011), and TPS2 is also upregulated (Ogawa, DeRisi and Brown, 2000). In these conditions, central carbon metabolism is down, and phosphate limitation is a ‘general starvation’ cue (Brauer et al , 2008; Boer et al , 2010; Gurvich, Leshkowitz and Barkai, 2017). Why this occurs has not been immediately apparent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a crisis, such as starvation, organisms should adapt at both individual (1,2) and population levels (3)(4)(5). In unicellular organisms, the former has been intensively studied as an adaptation phenomenon (11)(12)(13), whereas the latter is poorly understood. Severe conditions decrease the carrying capacity (6), and unicellular organisms have to decrease the population size (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…The molecular or mechanistic basis of these limitations, however, remained unclear. Gene expression signature is a sensitive probe of internal limitations; Budding yeast experiencing amino acids limitation, for example, induce GCN4-target genes (Gasch et al, 2000; Tamari et al, 2014), while cells depleted of internal phosphate induce PHO4 targets (Gurvich et al, 2017; Gutteridge et al, 2010). Both responses are gradual, providing a quantitative readout of the limitation.…”
Section: Introductionmentioning
confidence: 99%